Vascular access for hemodialysis: analysis of clinical data Diaverum in Sergipe (Research, Society and Development, 2022)
Patients with acute renal failure or end-stage chronic kidney disease require renal replacement therapy that can be performed by peritoneal dialysis, hemodialysis (HD), or kidney transplantation. Venous access is essential for hemodialysis and can be performed using Central Venous Catheters (CVC), arterialization of a native vein or by interposition of a graft. Several comorbidities such as diabetes, peripheral arterial disease, obesity and others negatively interfere with the success of vascular access, especially in native arteriovenous fistula. Previous use of CVC is associated with failure to make an AVF. When HD is the option, the creation of an FAV should be as brief as possible, with rare exceptions. Thus, the study aims to evaluate the epidemiological and clinical variables of patients undergoing arteriovenous fistula at the Diaverum institution, in the state of Sergipe, and comparatively analyze temporary and permanent vascular access . As a result, we could observe a higher rate of patients who started hemodialysis by CVC and a higher rate of complications was observed. In addition, it can also be noted that in patients who started treatment with AVF, there was a longer duration of the fistula in the long term than those who started with a catheter. With these results, we were able to conclude that every vascular access in the patient who has advanced CKD and in patients who already undergo hemodialysis must take into account several factors, and not only the practicality of implantation due to the consequences that it can cause in another access in the future.